Perancangan Papan Permainan Tentang Pentingnya Sayuran Berbasis Family Games Sebagai Sarana Pendidikan Anak-anak Usia 6-12 Tahun - Halim, M Rahadian; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
The design work of this thesis aims to teach the importance of vegetable benefits as a media education for children aged 6-12 years. The selected media educational board game because it can facilitate the learning process and absoroption of information to children because it’s supported by enjoyable atmosphere and also can grow familiarity. Using board game which is exciting and interactive as a safe learning media to convey information about the importance of vegetables would be more efficient. This game is peddled with attractive illustration to attract the interest of children who are the target audience.Keywords: Education, Vegetables, Family Games, Board Game and Children.